Genetic differentiation in Eurasian Woodcock (Scolopax rusticola) from the Azores. (20th July 2021) - Andrade, Pedro; Rodrigues, Tiago M.; Muths, Delphine; Afonso, Sandra; Lopes, Susana; Godinho, Raquel; Leitão, Manuel; Ferrand, Yves; Ferrand, Nuno; Gonçalves, David
Abstract : The Eurasian Woodcock Scolopax rusticola is a widespread Palaearctic migratory wader, with purportedly sedentary populations occurring in the Macaronesian archipelago of the Azores. Here we used microsatellite markers to investigate patterns of genetic diversity and differentiation in these insular birds, and compared Azorean populations with those from mainland Europe. Azorean populations show a (non‐significant) trend for reduced diversity, and low but consistent differentiation from mainland populations; evidence for widespread over‐water migration (in either direction) is weak but must occasionally occur given the recovery of an Azorean ringed bird in France. It is thus likely that the Azorean populations diverged recently from their mainland counterparts, but gene flow is currently restricted.